Industri Bioplastik Starch-Cellulose Blend Tandan Kosong Kelapa Sawit dalam Pemenuhan Sustainable Development Goals - Tsaniyah, Legis; Bantacut, Tajuddin; Suprihatin, Suprihatin (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Indonesia is the world’s second largest contributor of plastic waste entering the oceans, where it degrades into microplastics smaller than 1 micron. The use of bioplastics is therefore essential to mitigate environmental pollution. One promising alternative is starch–cellulose blend bioplastic derived from empty fruit bunches (EFB) of oil palm. Indonesia produces about 56.35 million tons of EFB annually, containing approximately 40% cellulose, which makes it a potential raw material for bioplastic production, although commercialization has not yet been realized. Environmentally, converting EFB into bioplastics within the palm oil value chain represents a sustainable waste recycling strategy that transforms solid residues into higher-value products. In this design, soda cooking technology is employed to extract cellulose from EFB, utilizing about 16% of waste from a crude palm oil (CPO) mill with a capacity of 30 tons of fresh fruit bunches (FFB) per hour. The starch–cellulose blend bioplastic pellets are formulated using gelatinized cassava starch as the polymer matrix, glycerol as a plasticizer, polyvinyl alcohol (PVA) as a stabilizer, and cellulose as a filler. The designed production capacity of the EFB-based starch–cellulose bioplastic plant is 16,500 tons per year. This bioplastic industry is expected to contribute positively to achieving eight Sustainable Development Goals (SDGs), including Goals 1, 8, 9, 12, 13, 14, 15, and 17, thereby supporting Indonesia’s commitment to sustainable industrial development and a cleaner environment.